The efficacy of CT for detection of right ventricular dysfunction in acute pulmonary embolism, and comparison with cardiac biomarkers - In, Erdal; Aydin, Ayse Murat; Ozdemir, Cengiz; Sokucu, Sinem Nedime; Dagli, Mustafa Necati (Springer, 2015)
Purpose The purpose of this study was to evaluate results from computed tomography pulmonary angiography (CTPA) indicative of right ventricular dysfunction (RVD), and to assess the relationship of these results with cardiac biomarkers and mortality among patients with acute PE. Materials and methods This retrospective study involved 118 patients with acute PE proved by CTPA. CTPA variables were analyzed and compared with cardiac biomarkers and echocardiography (ECHO) findings. Results Compared with ECHO, the sensitivity, specificity, positive predictive value, and negative predictive value of CTPA for detection of RVD were 85.7, 91.7, 93.7, and 81.5 %, respectively. ROC curve analysis for prediction of RVD resulted in areas under the curve of 0.925 for RV dimension (95 % CI 0.879-0.971, p < 0.001) and 0.913 for main pulmonary artery (MPA) diameter (95 % CI 0.863-0.963, p < 0.001). The optimum cut-off values for prediction of RVD were 37.5 mm for RV dimension and 29.1 mm for MPA diameter. These values were also statistically significantly greater for non-survivors than for survivors (p = 0.001, p < 0.001, respectively) and significantly associated with cardiac biomarkers. Conclusion It was found that CTPA findings were significantly associated with the presence of RVD in ECHO, cardiac biomarkers, and mortality of patients with acute PE.
Keywords: Computed tomography pulmonary angiography (CTPA); Pulmonary embolism (PE); Right ventricular dysfunction (RVD); Cardiac biomarkers